Blog-based online journals for English As A Second Language learners - Ngah, Ezihaslinda (2007)
The research on the use of blogs as online journals was carried out with a group of twenty five Form Four students in a secondary school in Kuantan, Pahang. The aim of the research is to find out the effects of blogs as a tool in developing writing in English as A Second Language. The instruments include questionnaire, semi-structured interviews and analysis of the blogs content. The research covered students’ perspectives of blogs as the medium for online journals, the effectiveness of blogs as a tool to assist students’ writing skill and to what extent blogs could help students to enhance their writing skills. From the findings, it is discovered that there is a positive impact on the development of students’ writing throughout the research as gained through the instruments. From the research, the students claimed that blogs is an interesting medium for them to write their journals as compared to writing in their log books. Blogs also could help them developed their writing skill in English Language; and through the various features in blogs, students were able to write more effectively.